Indonesia-INTERASPIRE study: an Indonesian cross-sectional multicenter survey on cardiovascular secondary prevention in coronary heart disease - Ambari, Ade Meidian; Hasan, Harris; Dwiputra, Bambang; Desandri, Dwita Rian; Hamdani, Rita; Krevani, Citra Kiki; Syaoqi, Muhammad; Ridwan, Muhammad; Anandini, Hesti; Fitra, Maha; Arso, Irsad Andi; Anggraeni, Vita Yanti; Hartopo, Anggoro Budi; Siregar, Yasmine Fitrina; Tjahjono, Cholid Tri; Tiksnadi, Badai Bhatara; Febrianora, Mega; Tarsidin, Najmi Fauzan; Arityanti, Dean; Qhabibi, Faqrizal Ria; Makes, Indira Kalyana; Susilowati, Eliana; Erwan, Nabila Erina; Hergaf, Indah Widyasari; Raynaldo, Abdul Halim (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Cardiovascular disease (CVD) is projected to affect more than 23.3 million people by 2030. Therefore, CVD prevention strategies were established to decrease morbidity and mortality while enhancing overall well-being. The Joint European Societies (JES) guidelines on CVD prevention were developed to enhance preventive cardiology practices. This study aimed to evaluate the adherence to JES guidelines for cardiovascular prevention in routine clinical practice for secondary prevention. METHODS This multicenter cross-sectional study was conducted in 7 centers between August 2020 and June 2021. Patients under 80 years old who had undergone percutaneous transluminal coronary angioplasty, coronary artery bypass graft, percutaneous coronary intervention, or experienced acute coronary syndrome were identified from medical records and interviewed a year later. Descriptive statistics were used to calculate the occurrence of risk variables, medication use, and index events associated with low-density lipoprotein cholesterol (LDL-C), hemoglobin A1c, and blood pressure (BP). RESULTS A total of 402 participants (13.9% female) were interviewed, and their medical records were reviewed. Among the study population, 74.4% had a smoking history, 35.4% had dyslipidemia, 33.1% did not meet the BP target, and only 28.4% achieved the LDL-C target. Additionally, less than half (43.8%) participated in physical activity for >150 min/week. Only 15.6% of the patients among the centers who had scored >8 for the guideline-based target score. CONCLUSIONS Most patients did not meet the guidelines for secondary prevention, primarily due to the high prevalence of dyslipidemia and physical inactivity, although some achieved the LDL-C target.